2006
DOI: 10.1111/j.1527-3458.2006.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

A‐85380: A Pharmacological Probe for the Preclinical and Clinical Investigation of the α4β2 Neuronal Nicotinic Acetylcholine Receptor

Abstract: A-85380 [3-(2(s)-azetidinylmethoxy) pyridine] is a neuronal nicotinic acetylcholine receptor (nAChR) agonist that has been a useful tool in the investigation of the function of nAChRs in both preclinical and clinical studies. Amongst nAChR subtypes, A-85380 shows selectivity for the á 4 â 2 vs. the á 7 or á 1 â 1 äã nAChRs. In functional in vitro cation flux assays, A-85380 is a potent and full agonist. A-85380 has a broad-spectrum analgesic profile with efficacy in acute, persistent, and neuropathic pain mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Recently, an α 4 β 2 -subtype-selective radioligand, 3-[2(S)-2-azetidinylmethoxy]pyridine (A-85380) has been developed for in vivo quantification of α 4 β 2 nAChRs using PET Brody et al 2006;Chefer et al 2003;Mitkovski et al 2005; and single photon emission computed tomography imaging (Mitsis et al 2007;O'Brien et al 2007;Staley et al 2005;Ueda et al 2004). The radioligand A-85380 has high affinity (K i =0.048 nM) for α 4 β 2 nAChRs (Rueter et al 2006). Using this ligand, we recently showed no significant differences in regional nAChR distribution volume (DV S ) between drug-naïve early AD patients and healthy age-matched controls (Ellis et al 2008), although Brody et al (2006) recently reported significant (up to 88%) occupancy of α 4 β 2 nAChRs by nicotine following cigarette use, suggesting potential modulation by nicotinic receptor agonists.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, an α 4 β 2 -subtype-selective radioligand, 3-[2(S)-2-azetidinylmethoxy]pyridine (A-85380) has been developed for in vivo quantification of α 4 β 2 nAChRs using PET Brody et al 2006;Chefer et al 2003;Mitkovski et al 2005; and single photon emission computed tomography imaging (Mitsis et al 2007;O'Brien et al 2007;Staley et al 2005;Ueda et al 2004). The radioligand A-85380 has high affinity (K i =0.048 nM) for α 4 β 2 nAChRs (Rueter et al 2006). Using this ligand, we recently showed no significant differences in regional nAChR distribution volume (DV S ) between drug-naïve early AD patients and healthy age-matched controls (Ellis et al 2008), although Brody et al (2006) recently reported significant (up to 88%) occupancy of α 4 β 2 nAChRs by nicotine following cigarette use, suggesting potential modulation by nicotinic receptor agonists.…”
Section: Introductionmentioning
confidence: 98%
“…In pharmacologically relevant antidepressant, anti-nociceptive, and anti-allodynic doses (0.1-1 mg/kg), A-85380 shows considerably lower toxicity than nicotine and epibatidine (Curzon et al, 1998;Rueter et al, 2003Rueter et al, , 2006Buckley et al, 2004). This drug easily penetrates the blood-brain barrier, and in mice has a relatively long half-life (more than 1 h) (Curzon et al, 1998) compared with nicotine that has a halflife of few minutes (Damaj et al, 2007).…”
Section: A-85380 Reproduces the Action Of Varenicline On Cortical Dnmmentioning
confidence: 99%
“…To establish whether a 4 b 2 nAChR stimulation is responsible for the epigenetic modifications in mice caused by nicotine and VAR, we administered A-85380, an agonist Selective a 4 b 2 nicotinic acetylcholine receptor agonists E Maloku et al that binds with subnanomolar affinity to a 4 b 2 but has negligible affinity for a 3 b 4 -or a 7 subtype-containing receptors (Smith et al, 2007;Rueter et al, 2006). In pharmacologically relevant antidepressant, anti-nociceptive, and anti-allodynic doses (0.1-1 mg/kg), A-85380 shows considerably lower toxicity than nicotine and epibatidine (Curzon et al, 1998;Rueter et al, 2003Rueter et al, , 2006Buckley et al, 2004).…”
Section: A-85380 Reproduces the Action Of Varenicline On Cortical Dnmmentioning
confidence: 99%
“…Competition binding studies with the α 7 -nicAchR selective ligand [ 3 H]-MLA were conducted in rat hippocampal membranes [16, 18]. In contrast to nicotine and lobe-line, lobinaline has similar affinity at α 4 β 2 - and α 7 -nicAchRs ( see Table 2 for comparison ) [80, 81]. Lobinaline produced a DDR value of 1.32, virtually identical to that produced by the CHCl 3 fraction, indicating lobinaline was the main metabolite responsible for the fraction’s nicAchR binding activity.…”
Section: Resultsmentioning
confidence: 99%
“…The alkaloid inhibited binding of the α 4 β 2 -nicAchR selective ligand [ 3 H]-cytisine (K i = 1.066 μM), and the α 7 -nicAchR selective ligand [ 3 H]-MLA (K i = 67.53 μM), in rat cortical and hippocampal membranes, respectively, and produced a DDR value of 1.32 [1, 1618]. Compared to other plant metabolites, such as nicotine and lobeline, lobinaline is relatively non-selective with respect to α 4 β 2 - and α 7 -nicAchRs ( see Table 2 for comparison) [80, 81]. The plant metabolite anabasine is also non-selective at α 4 β 2 - and α 7 -nicAchRs (K i = 65 nM and 58 nM at α 4 β 2 - and α 7 -nicAchRs, respectively) [1].…”
Section: Discussionmentioning
confidence: 99%